(untitled) (Research in Agriculture Livestock and Fisheries, 2026)
Youth participation in agriculture is recognized as a pathway to employment, food security, and economic empowerment. This study examined the socio-economic characteristics of youth involved in backyard farming, as well as the challenges and opportunities influencing their participation in Dzwerani Village, South Africa. A quantitative survey was conducted among youth participants engaged in backyard farming. Descriptive statistics were used to analyze demographic characteristics, farming activities, income sources, challenges, and perceived opportunities. The findings showed that most participants were between 21 and 35 years of age, with male youth dominating participation. Most of the participants had completed their secondary and tertiary education. Livestock production was the most common agricultural activity, and most participants farmed for both income generation and household consumption. The study identified the following challenges: lack of access to land, limited inputs, and financial constraints. On the other hand, key opportunities included income generation, food security, job creation, and entrepreneurship. The study highlighted the need for targeted policies and support programs to strengthen youth access to land, resources, and training, thereby enhancing their participation in agriculture. Res. Agric. Livest. Fish. Vol. 13, No. 1, April 2026: 23-30